Geographical Indications and Traditional Specialities: Case Study of Poland - Inga Oleksiuk; Agnieszka Werenowska (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The contemporary development of rural areas requires verified agricultural production and support for manufacturing of traditional and regional high-quality products. The aim of the research described in this article has been to assess customer awareness of these products and to identify the features attributed to them in view of existing legal regulations. A catalogue of currently binding regulations has been established, taking account of their axiological assumptions, and results of a survey have been analysed. An assessment of the law functioning in this area has allowed the conclusion that a simplification of the existing regulations and procedures is needed. This is the precondition for the axiological assumptions of the said regulations to be fulfilled. The weight of the discussed subject has been proven by the results of the conducted survey: 93% of the respondents declared buying the described products. The quality of the products, as well as the respondents’ pride in the indigenous culinary tradition, were the main reason for their choice (54%). Examining the laws in the discussed area requires adoption of an interdisciplinary axiological perspective.